Lithuanian science courses in Vilnius and traces of mathematics in them - Banionis, Juozas (Lietuvos matematikos rinkinys, 2019)
Lithuania and sheds light on attempts by the Lithuanian public to revive higher education studies in Vilnius from 1919 to 1921. According to the remaining sets of documents it is possible to testify about the existing traces of mathematics in the projects of the restored Vilnius University or organized higher education courses.
Keywords: Vilnius University; Lithuanian science courses; mathematics studies; history of mathematics